Neurofeedback: a new therapeutical perspective for Psychiatric Disorders as an alternative to excessive psychotropics consumption - Santos, Iolanda Mendes (2016)
Psychiatric Disorders are known as a major contributor for comorbidity worldwide. The roles of stress, anxiety and sleep disturbances are considerable factors in the process of instability of mental health integrity. Despite the efforts continuously made to control the growing prevalence of such disorders, there are still emerging issues at the time of giving a proper diagnosis, choosing the best therapeutic option and dealing with adverse effects and resistant symptoms. Depressive and anxiety disorders as well as attention deficit hyperactivity disorder (ADHD) are regarded here as mental disorders with similar factors influencing the health disease process. Allopathic medicine with the resource of psychotropics and psychotherapy to deal with mental disorders are facing the growth of substance dependence dilemma. This is due to the prolonged use of psychotropic medicine, improper use, abuse and inefficient monitoring. Psychotropic consumption is increasing on a larger scale at the present time and known as a major contributor for comorbidity. The guidelines recommend the use of methylphenidate as well as psychotherapy to treat ADHD. Methylphenidate is a stimulant medicine, belonging to the psychotropic group of medication, which the mechanism is not completely understood. Many children have shown to be resistant to these treatments or to suffer from side effects related to the use of the medication. Moreover, the side effects of psychotropics use on children’s mood and behavior are a major topic of concern in this field. To contribute to a better approach towards psychotropic misuse, this dissertation aims to stimulate the use of alternative techniques for both diagnose and treatment of children with ADHD. Symptoms like impulsivity, hyperactivity, and lack of attention and focus, can directly influence the child’s life in school, home and social skills. Despite of the high prevalence of this disorder and of years of research there is still a marked uncertainty regarding both its diagnose and treatment. Through online research on database websites like PubMed, Medscape and Science Direct, documental research, analyzing and gathering data it is recognized that Neurofeedback is a very promising tool. The criteria for filtering information is based on the English language articles, the Diagnostic and Statistical Manual of Mental Disorder (DSM), as well as the American Academy of Child and Adolescent Psychiatry practice guidelines. The search phrases used were biofeedback, neurofeedback, psychiatric disorders, attention deficit hyperactivity disorder and cognition. Neurofeedback training is a safe and noninvasive method that can be tailored for each patient according to a baseline quantitative electro encephalogram (qEEG) analysis of the brain. This technique functions through operant conditioning training, which is through an immediate visual and auditory feedback each time the brain emits the correct level of brainwaves. This enables the patientto subconsciously change his/her brain activity, leading to behavioral changes towards the norm. A certain amount of neurofeedback sessions will eventually induce plasticity in appropriate areas of the brain. Therefore, the most appropriate electrophysiological patterns will be permanently restored. Our analytic review indicated that the qEEG pattern of children with ADHD has a significantly higher ratio level of theta: beta in the frontal cortex, compared to normal children. Using this information, clinicians are able to accurately diagnose children with ADHD, and at the same time to expose them to a proper neurofeedback training protocol. This would rebalance their brain waves in the affected areas of the brain. This method have led to remarkable improvements in inattention and impulsive behaviors of children with ADHD. In some cases, reduction or even in the termination of taking the medication.